Impact of Front Line Demonstrations on Yield Enhancement of Cumin: A Case in Arid Zone of Rajasthan - M LMeena , Dheeraj Singh, N.K. Sharma (Indian Journal of Extension Education, 2022)
Cumin ( Cuminum cyminum L.) is a predominantly rabi crop of arid zone of Rajasthan. The crop accounts for 32.21 and 18.09 per cent of area and production, respectively, in Rajasthan. However, the average district yield is 7.76 q./ha.,which is substantially lower than the national average (12.45 q./ha.). Considerable scope of enhancement in productivity leading to higher production exists, especially in Pali in arid zone, which is earmarked as importantAgro Export Zone for cumin in the country. To demonstrate this, 65 Front Line Demonstrations (FLDs)were organized by KrishiVigyan Kendra (KVK), Central Arid Zone Research Institute (CAZRI), Pali between 2004-05 and 2008-09 at five locations under actual farm situations. The economics and cost benefit ratio of both control and demonstrated plot was worked out. An average net profit of Rs. 92700 was recorded under recommended practices while it was Rs. 64825 under farmers practice. Cost : benefit ratio was 2.02-3.94 under demonstration, while it was 1.49-2.86 under control plots. By conducting FLDs of proven technologies, yield potential and net income from cumin production technology can be enhanced to a great extent with an increase in the income level of the farming community.